About applying of Gauss plane to human gait assessment - Jaworek, Krzysztof; Pauk, Jolanta (European Journal of Clinical and Experimental Medicine, 2005)
<span style="color: #010101; font-family: Lato, sans-serif; font-size: 14px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-align: justify; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The aim of this paper is presentation a new method to assessment of human gait using model’s coefficient obtained from regression function and Gauss plane.